Biomechanical effects of different materials for an occlusal device on implant-supported rehabilitation in a tooth clenching situation: A 3D finite element analysis - Andrade, Carla Souza; de Abreu Costa, Luy [UNESP]; Menechelli, Luana Gonçalves [UNESP]; Lemos, Cleidiel A. A.; Okamoto, Roberta [UNESP]; Verri, Fellippo R. [UNESP]; de Souza Batista, Victor Eduardo [UNESP] (Wiley, 2024)
Purpose: The purpose of this 3D finite element analysis was to evaluate the biomechanical effects of different materials used to fabricate occlusal devices to achieve stress distribution in simulated abutment screws, dental implants, and peri-implant bone tissue in individuals who clench their teeth. Materials and Methods: Eight 3D models simulated a posterior maxillary bone block with three external hexagon implants (Ø4.0 × 7.0 mm) supporting a 3-unit screw-retained metal-ceramic prosthesis with different crown connection (splinting), and the use of an occlusal device (OD). The OD was modeled to be 2-mm thick. ANSYS 19.2 software was used to generate the finite-element models in the pre-and post-processing phases. Simulated abutment screws and dental implants were evaluated by von Mises stress maps, and simulated bone was evaluated by maximum principal stress and microstrain maps by using a finite element software program. Results: The highest stress values in the dental implants and screws were observed in single crowns without OD (M1). Furthermore, the highest stress values and bone tissue strain were found in single crowns without OD (M1). The simulated material for the OD did not cause many discrepancies in terms of the stress magnitude in the simulated dental implant and abutment screw for both single and splinted crowns; however, more rigid materials exhibited lower stress values. Conclusion: The use of OD was effective in reducing stress in the simulated implants and abutment screws and stress and strain in the simulated bone tissue. The material used to simulate the OD influenced the biomechanical behavior of implant-supported fixed prostheses, whereas splints with rigid materials such as PEEK and PMMA exhibited better biomechanical behavior.
Keywords: biomechanical phenomena; dental implants; finite element analysis